Analysis of the grinding wheel wear and machining result during cutting edge preparation with elastic bonded grinding wheels. (March 2022) - Hartig, Jörg; Kirsch, Benjamin; Aurich, Jan C.
Abstract: Cutting edge preparation can be considered as one of the most effective methods for optimizing the cutting tool life and the machining result. In this article, a preparation technique using elastic bonded superabrasive grinding wheels is applied. This method proved to be highly flexible in terms of the achievable cutting edge geometry. However, very little knowledge exists about the grinding wheel wear behavior and therefore the process reliability during cutting edge preparation. In this article, the impact of the process kinematics and parameters on the grinding wheel wear and preparation result is investigated and discussed. For this purpose, the impact of the depth of cut (20, 40 and 60 μm) was investigated, because it serves as the major setting parameter for the size of the cutting edge rounding. However, it also impacts the contact conditions and thermo-mechanical loads in the grinding wheel. The experimental results show that this preparation method achieves a high preparation accuracy and repeatability at small and medium depths of cut (20 and 40 μm). For a depth of cut of 60 μm, the preparation result became more inappropriate (increased deviation of the cutting edge shape from an ideal radius) with an increasing number of prepared cutting edges. Here, the soft grinding wheel exhibited a higher process stability in terms of repeatable machining results. The machining results correspond to the experimental findings from the grinding wheel radial wear Δrs . At a depth of cut of 20 and 40 μm, the grinding wheel radial wear for the hard bond was lower than for the soft bond. At a depth of cut of 60 μm, the grinding wheel radial wear for the hard bond exceeds the value for the soft bond by 10%. However, the grinding (G) ratios for the hard bond were higher for all investigated depths of cut. The highest difference was observed at a depth of cut of 20 μm. Here, the G ratio for the soft grinding wheel was 7.92 and for the hard one 18.53. Furthermore, an application scenario was introduced using suitable dressing cycles, so that up to 138, 000 cutting edges (equals 34, 500 indexable inserts) could be prepared with one grinding wheel using this preparation technique in industrial tool manufacturing applications.